2006
DOI: 10.1523/jneurosci.1413-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Cocaine Self-Administration Alters Processing of Cocaine-Related Information in Rat Prefrontal Cortex

Abstract: One of the core symptoms of cocaine addiction is compulsive drug-seeking behavior. Although the precise neural substrates are unknown, it has been hypothesized that this behavior involves cocaine-induced hypofunction of the prefrontal cortex (PFC) or "hypofrontality." To test this hypothesis, PFC neuronal activity was monitored in rats during ϳ3 weeks of cocaine self-administration (SA). Rats were trained to press a lever to self-administer cocaine in daily 2 h sessions. Responding was reinforced contingent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 27 publications
7
90
0
Order By: Relevance
“…The PFC and amygdala, especially the projections from the medial PFC and BLA to NAc, have been critically implicated in a large number of cocaine-induced behavioral alterations, such as increased impulsivity, cue-induced relapse, extinction, and reinstatement/relapse to cocaine administration (7,8,34). Neuroimaging studies in cocaine addicts revealed a reduced PFC activity under baseline conditions, which is paralleled by findings in cocaine self-administering rats (38,39). However, the PFC and NAc are hyperresponsive toward drug-associated cues or cocaine exposure both in humans and rats.…”
Section: Discussionmentioning
confidence: 78%
“…The PFC and amygdala, especially the projections from the medial PFC and BLA to NAc, have been critically implicated in a large number of cocaine-induced behavioral alterations, such as increased impulsivity, cue-induced relapse, extinction, and reinstatement/relapse to cocaine administration (7,8,34). Neuroimaging studies in cocaine addicts revealed a reduced PFC activity under baseline conditions, which is paralleled by findings in cocaine self-administering rats (38,39). However, the PFC and NAc are hyperresponsive toward drug-associated cues or cocaine exposure both in humans and rats.…”
Section: Discussionmentioning
confidence: 78%
“…For example, basal activity in the prefrontal cortex is blunted in human addicts and in animal models (12,15), and by restoring activity to the prefrontal cortex, N-acetylcysteine could decrease action potential-mediated synaptic glutamate release and elicit homeostatic down-regulation of AMPA receptors (41).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, animal models of relapse show that activation of this pathway is necessary and sufficient to reinstate cocaine-seeking behavior (13) and that neuronal activity in pyramidal neurons in prefrontal cortex projecting to medium spiny neurons (MSNs) in the nucleus accumbens core (NAcore) region is correlated with cocaine-seeking (14,15). Accordingly, it is thought that prefrontal-to-accumbens synapses undergo enduring potentiation after chronic cocaine use that contributes to relapse vulnerability (4,6,16).…”
mentioning
confidence: 99%
“…DA-dependent alteration of prefrontohippocampal circuits involved in the consolidation of events linked to the reward could thus account for the spatial deficit in drug-reinforced subjects. Interestingly, chronic intake of drugs of abuse induce a hypofrontality-like syndrome in animals (Jentsch and Taylor, 1999;Homayoun and Moghaddam, 2006;Sun and Rebec, 2006) and addicted humans (Goldstein and Volkow, 2002;Kalivas et al, 2005;Goldstein et al, 2007). Morphine-induced increases in DA release within other brain regions may have occurred: activation of the basolateral amygdala elicited by emotionally charged events impairs hippocampus-dependent learning and synaptic plasticity (Akirav and Richter-Levin, 1999;Kim and Diamond, 2002;Layton and Krikorian, 2002).…”
Section: Discussionmentioning
confidence: 99%